2022
DOI: 10.34172/mejdd.2022.263
|View full text |Cite
|
Sign up to set email alerts
|

Association between Melatonin Value and Interleukins1B, -18, and -33 Levels in Patients with Different Stages of Non-Alcoholic Fatty Liver Disease

Abstract: BACKGROUND: Interaction between immune modulators and inflammatory factors is considered as one of the main underlying pathologies of non-alcoholic fatty liver disease (NAFLD). Hence we aimed to assess the association between these cytokines and melatonin. METHODS: We enrolled adult patients diagnosed with fatty liver by ultrasonography in a crosssectional study. All of them underwent Fibroscan evaluation. The subjects who met the inclusion and exclusion criteria for NAFLD were involved. A normal group who did… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The current study reveals a notable trend since participants who failed to improve their IFC over the 2-year intervention exhibited increased IL-18 plasma levels, while those who succeeded experienced significant reductions compared to the other group. This finding aligns with previous research demonstrating high serum IL-18 levels correlating with the progression of MAFLD and advancing fibrosis [74]. The relationship between plasma IL-18 levels and MAFLD progression, coupled with its association with renal injury, suggests the potential of IL-18 as a valuable biomarker in managing these metabolic conditions.…”
Section: Discussionsupporting
confidence: 90%
“…The current study reveals a notable trend since participants who failed to improve their IFC over the 2-year intervention exhibited increased IL-18 plasma levels, while those who succeeded experienced significant reductions compared to the other group. This finding aligns with previous research demonstrating high serum IL-18 levels correlating with the progression of MAFLD and advancing fibrosis [74]. The relationship between plasma IL-18 levels and MAFLD progression, coupled with its association with renal injury, suggests the potential of IL-18 as a valuable biomarker in managing these metabolic conditions.…”
Section: Discussionsupporting
confidence: 90%
“…One study detailing the beneficial role of MT in managing obesity demonstrated that MT supplementation stimulated thermogenesis in brown fat cells and attenuated lipogenesis in white fat cells and hepatocytes to support that MT can prevent the development or progression of MASLD caused by a Western-style HFD [171]. MT may also regulate feeding hormones such as ghrelin [20] and the inflammatory processes [172][173][174] that commonly contribute to obesity-related MASLD [20].…”
Section: Mt In the Gut-liver Axis Of Masldmentioning
confidence: 99%